Upaya Meningkatkan Prestasi Belajar Fiqih Melalui Model Pembelajaran Experience Skill Siswa Kelas IX MTs Swasta Yaspen Muslim Pematang Tengah - Fadilah, Umi; Al Qadri, Muamar; Sanusi Luqman, Ahmad (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2022)
The main factor that causes students to have difficulty learning jurisprudence is the lack of motivation both internal motivation and outside motivation. This can be seen from the learning process which shows that there are still many students who do not pay attention to the teacher who provides the subject matter. This study aims to determine efforts to improve the fiqh learning achievement of class IX MTs Private Yaspen Muslim Pematang Tengah students through the application of the Experience Skill Learning Model. The results showed that the cognitive abilities of class IX MTs. Yaspen Muslim students were very good as evidenced by the response of students who showed exemplary attitudes while participating in teaching and learning activities in the field of Jurisprudence studies. In the first cycle, some students are seen to be active in learning activities. Then, after the implementation of the Experience Learning learning model, students seem to be more active and responsive to the material being taught. The application of the Experience Learning model at the beginning of the meeting was ineffective because students had never participated in learning activities with the model. Then the learning model is applied through group discussion activities, direct practice and reflecting actions in each cycle. The application of this model goes well along with the ongoing learning and teaching activities by involving the participation of students as Student Oriented. The achievement of cognitive abilities of class IX MTs. Yaspen Muslim students has increased significantly after learning the field of Fiqh studies using the Experience Learning model.